Evaluation of growth performance and morpho-meristic characteristics in the progenies of Barbonymus gonionotus and Barbonymus schwanenfeldii - Mostamand, Jalaluddin; Esa, Yuzine (Malaysian Society of Applied Biology, 2024)
Recognizing the potential benefits of combining the favorable traits of both species, this study was designed to evaluate the culture performance and morphometric variations of F1 hybrids derived from artificial reciprocal hybridization between Barbonymus schwanenfeldii and Barbonymus gonionotus. Four crosses were successfully produced, namely B. gonionotus ♀ × B. gonionotus ♂ (GG), B. gonionotus ♀ × B. schwanenfeldii ♂ (GS), B. schwanenfeldii ♀ × B. schwanenfeldii ♂ (SS) and B. schwanenfeldii ♀ × B. gonionotus ♂ (SG). Uniform-sized fingerlings of pure GG, hybrid GS, pure SS, and hybrid SG were stocked at a rate of 50 fingerlings per fiberglass 1-tonne tank. The fingerlings were fed a commercial tilapia pellet (Dinding Malaysia) with 35% crude protein, the feeding was done twice a day, at 9:00 and 16:00, with equal portions given at each feeding. After 8 weeks of culture, the mean weight gained by GG, GS, SS, and SG was 7.09 ± 0.06, 5.75 ± 0.15, 4.69 ± 0.21, and 5.60 ± 0.17 g, respectively. The growth performance of the hybrid GS 5.75 ± 0.15 was significantly higher compared to the slow-growing SS (4.69 ± 0.21) but lower than the value recorded in GG (7.09 ± 0.06) under identical rearing conditions. A similar trend was observed in the final weight and specific growth rate (SGR) (%/day). In terms of FCR value, hybrid GS had the best value (1.10 ± 0.10) compared to hybrid SG (1.31 ± 0.13) or pure species (1.29 ± 0.09, 1.39 ± 0.13). Reciprocal hybrids showed intermediate morphometric traits between the two species; The reciprocal hybrids displayed intermediate morphometric traits that fell between the two parental species. The results of the discriminant function analysis confirmed that there were significant differences in the characters of all four species.